Establishing link between quality management and supply chain risk management: A fuzzy AHP approach. Issue 5 (22nd November 2019) - Ganguly, Kunal
Abstract : Purpose: The purpose of this paper is to present a comprehensive framework for quality-related performance measures linked to supply chain risk (SCR) by analyzing and framing them into a hierarchical structure. Design/methodology/approach: In this paper, quality-related performance measures (QM) are identified on the basis of literature survey and expert opinion. The quality measures are formulated as hierarchy structure and fuzzy AHP as a multi attribute decision-making tool is applied to judge the viable candidates. Findings: Based on a fuzzy AHP approach, a revised risk matrix with a continuous scale was proposed to assess the QMs' classes. The result classifies the QMs in different categories (extreme, high, medium and low). Based on this result, some management implications and suggestions are proposed. Originality/value: The present work proposes an assessment methodology for quality-related performance measures linked to SCR. The revised risk matrix with continuous scale for risk assessment in this field is a novel approach. This study contributes to the supply chain management and quality management literature, and provides suggestions for managers to adopt different strategies for different risk classes.